(untitled) (International Journal of Current Engineering and Technology, 2014)
Protected areas in Egypt suffer from severe negligence with regards to sustainable development. One of the reasons is the absence of the role of the planner, designer and evaluator, capable of evaluating protected lands, and convincing its residents and responsible organisations to draw up sustainable development plans, using the economic and environmental values of the land. This is because the residents prefer the economic value of the land only, as it achieves quick revenue by selling or by destructive exploitation of the environment. Often, this leads to encroachment on the land and natural areas of the reserve. Consequently, it affects the environmental systems present through the loss of the natural resources that should be protected. Examples of this include the clear encroachment of touristic activities in Sharm el Sheikh on the lower border of the Nabaq Reserve, the presence of a large commercial mall in the city of Shalatin to trade with the Sudan, in the center of Elba Reserve, the exploitation of the Nile Islands Reserve with residents building on the land, in addition to the attempt by the Housing Ministry to sell parts of the Petrified Forest Reserve to residents.The aim of this research is to show methods of evaluating land in general, and to find a method for evaluating protected areas both environmentally and economically, by creating a theoretical framework for the main elements used to evaluate protected areas. This is done through examining the profits resulting from a sustainable system that includes environmental, economic, social, and urban views, as well as those related to planning in one general framework, that provides the steps that all evaluators should follow when evaluating protected lands.The study shall apply this system to the Petrified Forest Reserve in New Cairo in Egypt to determine the aspects of negligence and the problems, from which this area suffers; in addition, the principles of guidance are applied to prevent its deterioration in order to solve the problem of sustainability in this reserve.